2021
DOI: 10.19101/ijatee.2021.874084
|View full text |Cite
|
Sign up to set email alerts
|

A review on mobility models in disaster area scenario

Abstract: Disaster struck does not announce itself and people usually caught with the ad hoc situation. Disaster is divided into two types which are natural disasters and man-made disasters. Natural disasters happen because of a natural phenomenon or process such as earthquakes, tsunamis, typhoons and others. Manmade disasters happen as a consequence of technological or human hazards such train accident, traffic collision, aviation incident (plane crash), structural collapse and others. Such disaster struck events may c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Alternatively, [27] surveyed different multihop ad-hoc network paradigms, including mobile ad hoc networks (MANETs), vehicular ad hoc networks (VANETs), and DTNs, and discussed their importance in the context of disaster response. Reviews on routing and rescue entities' mobility models for MANETs in disaster-struck areas can be found in [28] and [29], respectively. Authors in [30] studied disaster recovery solutions from the perspective of users and network solutions such as device-to-device (D2D) and dynamic wireless networks (DWNs), respectively.…”
Section: A Related Surveys and Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, [27] surveyed different multihop ad-hoc network paradigms, including mobile ad hoc networks (MANETs), vehicular ad hoc networks (VANETs), and DTNs, and discussed their importance in the context of disaster response. Reviews on routing and rescue entities' mobility models for MANETs in disaster-struck areas can be found in [28] and [29], respectively. Authors in [30] studied disaster recovery solutions from the perspective of users and network solutions such as device-to-device (D2D) and dynamic wireless networks (DWNs), respectively.…”
Section: A Related Surveys and Reviewsmentioning
confidence: 99%
“…Indoor and outdoor non-image-based people counting technologies [18] LMR, LTE [25] Routing, MANETs [28] 2020 Autonomous decision-making systems, NFV, SDNs [26] UAV-assisted VANETs, routing protocols [36] 2021 Wireless technologies for resilient networks [33] Mobility models, MANETs [29] Fog computing, disaster evacuation [17] UAV path planning, network security [21] IoT-enabled flood SAR systems [34] Data-plane recovery mechanisms for packet-switched networks [35] 2022…”
mentioning
confidence: 99%
“…Alternatively, [24] surveyed different multihop ad-hoc network paradigms, including mobile ad hoc networks (MANETs), vehicular ad hoc networks (VANETs), and DTNs, and discussed their importance in the context of disaster response. A review on rescue entities' mobility models for MANETs in disaster-struck areas can be found in [25]. Authors in [26] studied disaster recovery solutions from the perspective of users and network solutions such as device-to-device (D2D) and dynamic wireless networks (DWNs), respectively.…”
Section: A Related Surveysmentioning
confidence: 99%
“…Wireless technologies for resilient networks [29] Mobility models, MANETs [25] Fog computing, disaster evacuation [16] UAV path planning, network security [19] IoT-enabled flood SAR systems [30] Data-plane recovery mechanisms for packet-switched networks [31] 2022 Paradigms, physical and networking layers, challenges This paper…”
Section: Year Main Focusmentioning
confidence: 99%
“…Because of its selfconfiguring, self-repairing, self-functioning, and selfrecovery network, MANET is simple to maintain [4,5]. Since MANET is a decentralized, infrastructureless network, users can configure dynamically wireless connections without an established infrastructure network [6,7]. Military operations like tactical networks and complex defence research were where MANET was first use in the context of application.…”
mentioning
confidence: 99%